Evidence for the Involvement of Monoaminergic Pathways in the Antidepressant-Like Activity of Cymbopogon citratus in Mice - Umukoro, Solomon; Ogboh, Somtochukwu I.; Omorogbe, Osarume; Adekeye, Abdul-lateef A.; Olatunde, Matthew O. (Drug Research, 2017)
Objectives Depression is a complex neuropsychiatric disorder, which affects the quality of life of the sufferers and treatment approach is associated with serious adverse effects and sometimes therapeutic failures. Cymbopogon citratus leaf (CC) has been reported to exert anti-depressant effect but its mechanism of action is yet to be elucidated hence, the need for this study.Methods The anti-depressant-like effect of Cymbopogon citratus aqueous leaf was evaluated using forced swim test (FST), tail suspension test (TST) and yohimbine-induced lethality test (YLT) in aggregated mice. Interaction studies involving p-chlorophenylalanine (pCPA), an inhibitor of serotonin biosynthesis and yohimbine, α2-adrenergic receptor antagonist were carried out to evaluate the role of monoaminergic system in the anti-depressant-like effect of CC. The effect of CC on spontaneous motor activity (SMA) was also assessed using activity cage.ResultsCymbopogon citratus (25 and 50 mg/kg, p.o.) demonstrated antidepressant-like activity devoid of significant stimulation of the SMA in mice. However, the antidepressant-like property of CC was significantly (p<0.05) attenuated by pretreatment with yohimbine suggesting involvement of noradrenergic pathway in the action of the extract. Also, pCPA reversed the anti-immobility effect of CC, indicating the role of serotonergic system in the mediation of its antidepressant activity. Moreover, CC (25 and 50 mg/kg) potentiated the lethal effect of yohimbine in aggregated mice, which further suggest the involvement of monoaminergic systems in its action.Conclusions The results of the study showed that C. citratus might be interacting with serotonergic and noradrenergic pathways to mediate its anti-depressant-like effect in mice.
Keywords: Cymbopogon citratus; anti-depression; serotonergic; noradrenergic